1990
DOI: 10.1097/00000658-199008000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Body Composition on the Metabolic Responses to Elective Colon Resection

Abstract: Advancing age tends to be accompanied by predictable changes in organ-system function and body composition, as well as an increased prevalence of various diseases. Our knowledge of the metabolic responses to surgical stress is derived largely from studies of young and middle-aged individuals. Whether these responses are altered in the elderly is not well established; the characteristic changes in metabolic function and body composition that occur in the elderly may limit their ability to respond adequately and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Patients were significantly younger and there were significantly more women in our remifentanil group. Regardless of the modest difference in age, which is not clinically relevant, previous studies suggest that age and sex have only negligible effects on neuroendocrine responses to surgery [12, 42, 43]. Thus, at present there is no evidence that these factors per se constitute confounders of tissue oxygenation and perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were significantly younger and there were significantly more women in our remifentanil group. Regardless of the modest difference in age, which is not clinically relevant, previous studies suggest that age and sex have only negligible effects on neuroendocrine responses to surgery [12, 42, 43]. Thus, at present there is no evidence that these factors per se constitute confounders of tissue oxygenation and perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Taux d'effort perçu, vieillissement, réponse cardiovasculaire, test de marche de six minutes increasing age has been established (4), making it imperative to evaluate the change in cardiovascular response of older adults to submaximal exercise (6MWT), necessary to carry out ADL. Hence, this study is aimed at evaluating the cardiovascular responses of community dwelling older adult to a 6MWT.…”
Section: Mots-clésmentioning
confidence: 99%
“…Cardiovascular response which is the reaction by the body to a specific influence subject to individual factors such as advancing age, heredity, gender and level of physical fitness (3). Studies have shown that advancing age is potentially the most contributor to the various causes of decline in the metabolic function (4). Ageing results in a decrease of muscle power and exercise capacity (5).…”
Section: Introductionmentioning
confidence: 99%
“…An interaction variable between group and age is also introduced to capture the differential effect of age between trauma and control group. Notably considerable emphasis was placed in the past [23,24] to find the significance of age on trauma status and its progression. The final data set has nine covariates.…”
Section: Data Description and Data Preparation: Trauma Data Setmentioning
confidence: 99%